If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -19 = 10x + -79 Reorder the terms: -19 + 6x = 10x + -79 Reorder the terms: -19 + 6x = -79 + 10x Solving -19 + 6x = -79 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -19 + 6x + -10x = -79 + 10x + -10x Combine like terms: 6x + -10x = -4x -19 + -4x = -79 + 10x + -10x Combine like terms: 10x + -10x = 0 -19 + -4x = -79 + 0 -19 + -4x = -79 Add '19' to each side of the equation. -19 + 19 + -4x = -79 + 19 Combine like terms: -19 + 19 = 0 0 + -4x = -79 + 19 -4x = -79 + 19 Combine like terms: -79 + 19 = -60 -4x = -60 Divide each side by '-4'. x = 15 Simplifying x = 15
| 10m=(3m-11)-17 | | -2x^3+19X^2-38x+21=0 | | z=2z-68 | | 3x-11=2(x-3)-8 | | -26+17= | | 1=-3xy | | 4t+5=2 | | 3(1-2x)=6-6x | | 16+-12+-7= | | x^2+X(c-b)+(c-a)(a-b)=0 | | 4x-90=3x-60 | | 5x+3y=56 | | abc-cba=973 | | -9x+1=-26 | | abc-cba=891 | | 4*sinx*cosx+2*cosx+1=0 | | abc-cba=675 | | 3a+7+2a=18-9 | | abc-cba=456 | | 15z-75=180 | | x-11=4x+44 | | 6(x-3)=2(3x-5) | | 4t-66=5t-87 | | sin(2x)+2*cosx+1=0 | | X^4-x^3-27x^2+25x+50=0 | | 4(5x-3)=2x-34 | | 8q-67=6q-35 | | 3(c+5)=2(c+3)-11 | | 3q-132=180 | | sen(2x)+2*cosx+1=0 | | 6s-90=180 | | x+11=2(3x-2) |